Therapeutic plasma exchange for myasthenia gravis, Guillain-Barre syndrome, and other immune-mediated neurological diseases, over a 40-year experience. (3rd October 2022) - Fernández-Fournier, Mireya; Kerguelen, Ana; Rodríguez de Rivera, Francisco Javier; Lacruz, Laura; Jimeno, Santiago; Losantos, Itsaso; Hernández-Maraver, Dolores; Puertas, Inmaculada; Tallon-Barranco, Antonio; Viejo, Aurora; Frank García, Ana; Díez-Tejedor, Exuperio
ABSTRACT: Background: Therapeutic plasma exchange (TPE) was first used in neurology in the 1980s for myasthenia gravis (MG) and Guillain-Barré syndrome (GBS). Indications have since grown. Fear of complications with this treatment modality limit its use. Research design & methods: A study of patients undergoing TPE for neurological diseases (1981–2020) in a University Hospital in Madrid, Spain. Clinical indications, complications, procedure number, apheresis technique and replacement fluids were prospectively recorded and retrospectively analyzed. Historical trends were studied. Results: 159 patients (48.69 ±18.15 years, 54.3% females) underwent TPE using central-venous catheter and replacement fluid albumin. We performed 1207 procedures over 189 cycles (6.4 ±3.8 procedures/cycle). Most patients underwent TPE for category I–II indications, mainly GBS and MG (77.7%). Complication rate was low (3.9% procedures), mostly hypotensive/vasovagal reactions (55.3%) and vascular access-related complications (38.3%). Most were mild-moderate (92.9%), permitting TPE completion, and somewhat more frequent during the first procedure (38.3%) and after periods of little TPE use. GBS patients were more prone to complications than MG patients (6.5% vs. 1.2%, p<0.001) mainly hypotensive/vasovagal reactions (3.7% vs. 1.0%, p=0.008). Conclusions: TPE is well-tolerated with low complication rate (<4% procedures), mainly hypotensive/vasovagal reactions. Patients with GBS seem more prone to them than MG patients. Acquaintance with this technique seems necessary.